Aelfric and the cult of saints in late Anglo-Saxon England - Gretsch, Mechthild (Cambridge studies in Anglo-Saxon England ;, 2005)
"In this study, Gretsch analyses Aelfric's Lives of five important saints in the light of their cults in Anglo-Saxon England, namely Gregory, the Roman pope; Benedict, the founder of western Monasticism; Cuthbert, the Northumbrian saint; Swithun of Winchester; and Aethelthryth of Ely. This analysis gives the reader glimpses of 'Aelfric at work': he adapts the cults and rewrites the received Latin hagiography of the five saints, with the result that each of their English Lives conveys a distinct message to the contemporary political elite and to a lay audience at large."--Jacket